PENGARUH PERKEMBANGAN FASHION TERHADAP GAYA BERBUSANA (STUDI KASUS MAHASISWA FAKULTAS TEKNIK UNG) - ., Rahmatiah (Sainstek, 2009)
The research is aimed to know the effect of increasing of fashion to the clothing style of University student at FT UNG. The existence of fashion as view as thing that has side good-worse, beautiful-bad, praise-insult, productive-consumptive. The inclination of fashion become a part of life, because it must be inspect, known, and followed. Every body have right to determine their choose based on ethical and aesthetics of clothing. The increasing of fashion very effect to clothing style of University student at FT UNG. The matter was got from correlation result of examination moment person with remark r = 0,89 that significant on honestly standard. This matter was show relationship between increasing of fashion to the clothing style of university student at FT UNG is 80 %. From result statistic count with use real standard 0,05 get result ttabel= 1,6723 < t count = 15,7 > 1,6723 with free degree, examination criteria 15,7> 1,6723.This result between increasing to the significant effect because remark tcount = 15,7 >1,6723 is outside of equals area HO means that there is significant effect between increasing fashion to clothing style of university student at FT UNG.